Analysis of Indonesia's Foreign Policy in the Face of Climate Change: A Review from an International Relations Perspective - Rakuasa, Heinrich; Dzaka A Faris; Philia Christi Latue; Yamres Pakniany (Journal of International Multidisciplinary Research, 2024)
This research analyzes Indonesia's role in addressing the challenges of climate change from a foreign policy perspective, highlighting the factors that influence policy formation, the diplomacy strategies implemented, as well as their impact at the global level. With a comprehensive review, this research aims to provide insights into how Indonesia interacts with the international community in an effort to address the global environmental crisis. Through an exploration of the internal and external factors that influence foreign policy on climate change, the article identifies the challenges faced as well as the opportunities that exist for Indonesia to play a more active role in shaping the global environmental agenda. By highlighting Indonesia's contributions to climate change mitigation and adaptation as well as its environmental diplomacy efforts, this article provides a better understanding of the complex dynamics between Indonesia's foreign policy and climate change issues in the context of international relations.